Especies de Trips (Thysanoptera: Thripidae) mas comunes en invernaderos de flores de la sabana de Bogota - Cardenas, E.=700 1 Corredor, D.
(Es, En)
Ilus., 16 ref.
Keywords: THYSANOPTERA; THRIPIDAE; TAENIOTHRIPS; FRANKLINIELLA; TAXONOMIA; COLOMBIA; CLAVES Y ESQUEMAS; AGRONOMIA COLOMBIANA